Water Policy in the Philippines Issues, Initiatives, and Prospects - Hall, Rosalie Arcala; Pulhin, Juan M; Rola, Agnes C (Cham, Switzerland Springer International Publishing Imprint: Springer, 2018)
This book describes challenges in the policy and practices of the various water sectors in the Philippines that have led to water conflicts. Such conflicts arise in the nature of rural-urban competition, trans-administrative boundary issues, and inconsistencies between customary and state rules, and even within state rules. Using inter-, multi- and trans-disciplinary approaches, and analysing from various scales - community, local and national governments - the book discusses policies and strategies needed towards achieving water security especially for the poor. Reflective of the complex and urgent water policy and governance issues in many developing countries, the book offers valuable lessons and insights to policy makers, water sector managers, planners and regulators as well as to academics, researchers and students. .
1. Water resources in the Philippines: overview and framework of analysis -- 2. Water supply, demand and uses and the drivers of change -- 3. Laws, institutional arrangements and policy instruments -- 4. Domestic household use and sanitation patterns in urban, urbanizing and rural settings -- 5. Industrial/commercial water use and pollution/disposal problems -- 6. Agricultural water management issues -- 7. Aquaculture/marine resources water management -- 8. Multiple/Integrated Water Resources Utilization -- 9. Sustaining water resources with environmental protection -- 10. National and local initiatives in addressing water supply, water quality and sustainability -- 11. Policies and institutional interventions for water demand management -- 12. Towards a more responsive water policy and practice: challenges and prospects.
Description based on publisher-supplied MARC data.
Keywords: Economic policy; Environmental economics; Environmental management; Hydrology; Sustainable development; Water resources development -- Philippines